Financial inclusion, shadow economy and financial stability: Evidence from emerging economies - Elsherif, Nevine Essam (AUC Knowledge Fountain, 2019)
This study analyzes the interrelation between financial inclusion, the size of the shadow economy (SE) and the level of financial system stability on a panel sample of 20 emerging economic from 2004-2014. Using on panel fixed effects Two-Stage Linear Regression (2SLS), we find that different levels of financial inclusion lead to different levels of financial stability, and the size of the SE can greatly influence this relationship. We use two models: one for assessing the SE-inclusion tradeoff and the other for assessing the stability-inclusion tradeoff respectively. To measure inclusion and stability, we have computed two different indices using the same methodology employed by Sarma (2008). Our main findings show that financial inclusion has no significant effect on the size of the SE, however, both inclusion and SE can significantly increase the level of financial instability. Other variables were found to have a significant positive relation with SE like income inequality, age dependency ratio and credit to government and state-owned enterprises. While, income levels, unemployment, secondary school enrollment, and trade openness had a significant negative effect on the size of the SE. Regarding the impact on our computed index of financial instability and its determinants, concentration in the banking sector, competition in the banking sector, concentration in the banking sector, and financial openness were found to have a positive effect on the level of instability. Income levels were found to have mixed effects on the three measures of financial instability, while broad money to GDP (%); as a proxy for size of financial sector, bank overhead costs; as a proxy of banks' inefficiency had significant negative effects on level of financial instability.